Multimedia Corpus of Russian Dialects of Udmurtia: Electronic Subcorpus of Spoken Speech - Vernyaeva, Regina A.; Zhdanova, Ekaterina A. (Cuadernos de Rusística Española, 2023)
The article presents a description of the electronic subcorpus of oral speech, which is an integral part of the multimedia Corpus of Russian Dialects of Udmurtia (http://dialect.manuscripts.ru). The subcorpus allows you to study dialect vocabulary not only by the methods of corpus linguistics, but also by the methods of linguistic geography and electronic lexicography. An important component of the subcorpus is the presence in it of audio recordings of oral dialect speech, which makes it possible to identify and analyze the phonetic and grammatical features of various dialects of the republic. Due to the fact that Udmurtia is a multilingual region, the study of audio recordings helps to identify the interaction of languages spoken in the republic. The speech of dialect speakers, presented in the form of audio recordings, as well as the results of marking this speech, are new language material that clarifies information about the lexical and semantic features of the Russian dialects of Udmurtia. The linguistic and geographical database module makes it possible to select all the answers to one of the questions of the program on which the corpus marking is based, the result is the display of this word on the electronic map of Udmurtia. The article presents the results of marking up audio recordings, examples of maps and dictionary entries compiled using the corpus manager.